Preventif TB Paru Melalui Edukasi Kepada Masyarakat Desa Kampung Delima - Elmi Asmawati; Darmawansyah Darmawansyah; Pupu Yuni Rahayu; Erniwati Erniwati; Parida Parida; Herlina Mayasari; Tasimah Tasimah (Jurnal Pengabdian Kepada Masyarakat, 2024)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium Tuberculosis which generally attacks the lungs. This risk of transmission can be caused by several factors, including insufficient knowledge about TB disease, therefore public knowledge plays an important role in preventing the transmission of tuberculosis, both directly and indirectly. The aim of this community service is to increase public knowledge and understanding by informing and educating the public as an effort to prevent pulmonary tuberculosis. The activity carried out by this service is health education about preventing pulmonary tuberculosis. The method used is lectures and discussions which are given pre-test before and post-test after the extension to determine the success of the extension. This activity took place on July 12 2024. From the results of the community activity, 70% of the 20 people who took part in the counseling knew about Pulmonary Tuberculosis, understood how to prevent and treat Pulmonary Tuberculosis obtained from the post test results. The results of service using lecture and discussion methods can increase community knowledge in Desa Kampung Delima, Kecamatan Curup Timur.